Crosstalk Between Astrocytes and Microglia: An Overview - Matejuk, Agata; Ransohoff, Richard M. (Frontiers in Immunology, 2020)
Based on discoveries enabled by new technologies and analyzed using novel computational tools, neuroscience can be re-conceived in terms of information exchange in dense networks of intercellular connections rather than in the context of individual populations, such as glia or neurons.. Cross-talk between neurons and microglia or astrocytes are has been addressed, however, the manner in which non-neuronal cells communicate and interact remains less well understood. We review this intriguing crosstalk among CNS cells, focusing on astrocytes and microglia and how it contributes to brain development and two neurodegenerative diseases: Alzheimer disease and GRN-FTLD and the most prevalent brain tumor, astrocytoma. The goal of studying these intercellular communications is to promote our ability to combat these incurable neurological disorders.